Rambles of a runaway from southern slavery - Goings, Henry, approximately 1810- (Carter G. Woodson Institute series., 2012)
Rambles of a Runaway from Southern Slavery tells of an extraordinary life in and out of slavery in the United States and Canada. Born Elijah Turner in the Virginia Tidewater, circa 1810, the author eventually procured freedom papers from a man he resembled and took the man's name, Henry Goings. His life story takes us on an epic journey, traveling from his Virginia birthplace through the cotton kingdom of the lower South, and upon his escape from slavery, through Tennessee and Kentucky, then on to the Great Lakes region of the North and to Canada. His Rambles show that slaves were found not only in fields but also on the nation's roads and rivers, perpetually in motion in massive coffles or as solitary runaways. A freedom narrative as well as a slave narrative, this compact yet detailed book illustrates many important developments in antebellum America, such as the large-scale forced migration of enslaved people from long-established slave societies in the eastern United States to new settlements on the cotton frontier, the political-economic processes that framed that migration, and the accompanying human anguish. Goings's life and reflections serve as important primary documents of African American life and of American national expansion, the Civil War, and Reconstruction. This edition features an informative and insightful introduction by Calvin Schermerhorn.